Epic in Aristotle and Vico - Stocker, Barry (Springer International Publishing, 2018)
Epic is discussed as a forerunner to the novel. Aristotle’s comments on Homeric epic in the Poetics and Rhetoric are fully explored, to establish a view of what epic is and its relation to public forms of speech. Giambattista’s New Science is discussed with regard to its philosophy of history, its account of poetry and the central role it gives to Homeric philosophy. This is discussed as partly the product of a growing novelistic culture in Vico’s time and as applying to main aspects of the novel including its relation both to epic discourse and the more variable discourse of everyday life.